Stepdog - Galland, Nicole (New York : William Morrow Paperbacks, 2015)
What's the difference between puppy love and dogged devotion? When Sara Renault fired Rory O'Connor from his part-time job at a Boston art museum, and in response, Rory--Irishman, actor, musician, reformed party-boy-- impulsively leaned over and kissed her . . . she kissed him back. Now, as Rory's visa runs out on the cusp of his big Hollywood break, Sara insists that he marry her to get a green card. In a matter of weeks they've gone from being friendly work colleagues to a live-in couple, and it's all grand . . . except for Cody, Sara's beloved dog from her troubled previous relationship. Sara's overattachment to her dog is the only thing she and Rory fight about. When Rory scores both his green card and the lead role in an upcoming TV pilot, he and Sara (and Cody) prepare to move to Los Angeles. But just before their departure, Cody is kidnapped--and it is entirely Rory's fault. Desperate to get back into Sara's good graces, Rory tracks Cody and the sociopathic dognapper to North Carolina. Can Rory rescue Cody and convince Sara that they belong together--with Cody--as a family? First they'll need to survive a madcap adventure that takes them through the heart of America.
Keywords: Dogs -- Fiction; Kidnapping -- Fiction; Romance fiction